Modern Trends in Education in the Era of Digitalization: Task and Prospects of Development - Elchin Gashimov; Veronica Pestova (Yayasan Ilomata, 2021)
The article suggests an overall review of modern technological trends in education. The authors aimed to figure out the objectives, benefits and obstacles of their development. The article deals with innovations, which have already been and are being implemented in education system with Industry 5.0 shortly ahead. The main aim is to determine social and cultural impact of rapid digitalization in the sphere of education. Research methods were based on deductive categories. Elements of descriptive and comparative analysis were applied for identification of major patterns and tendencies. The review given by the authors proves that education is one of the main challenges for authorities, teachers and students in terms of digitalization. The results of the research indicate the importance of new paradigm and reconsidering of educational environment in general. It involves technological, social and communicative aspects. Some conventional standards have become obsolete and we need to acknowledge the fact. Modern society is facing not only technological challenges but also the ones concerning attitude and skills. We can conclude that effective agreement between social and technological process can be reached if legal framework and standardized approaches are involved.